HSCT FOR INHERITED BONE MARROW FAILURE SYNDROMES - Darrigo Junior, Luiz Guilherme; Scheinberg, Phillip; Atta, Elias Hallack; Bonfim, Carmem (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
THE BRAZILIAN SOCIETY FOR BLOOD AND MARROW TRANSPLANTATION (SBTMO) PRESENTS THE BRAZILIAN GUIDELINES ON HEMATOPOIETIC STEM CELL TRANSPLANTATION